The Summer Is Coming: nocte and timeless Genes Are Influenced by Temperature Cycles and May Affect Aedes aegypti Locomotor Activity - Teles-de-Freitas, Rayane; Rivas, Gustavo B. S.; Peixoto, Alexandre A.; Bruno, Rafaela Vieira (Frontiers in Physiology, 2020)
Mosquitoes exhibit activity rhythms, crucial for the transmission of pathogens, under the control of a circadian clock. Aedes aegypti is one of the world’s leading vectors. For decades, several studies have linked the rise in ambient temperature with the increase in their activity. Here, we identify candidate genes whose expression is influenced by temperature cycles and may affect Aedes locomotor activity. We observed that timeless completely lost its rhythmic expression in light/dark, with out-of-phase temperature cycles, and by dsRNAi knockdown of nocte, an important gene for Drosophila circadian synchronization by temperature cycles. Thus, timeless and nocte are important genes for synchronization by temperature cycles in Aedes aegypti. To reinforce our findings, we simulated in the laboratory the gradual temperature fluctuations that were as close as possible to daily temperature variations in Brazil. We observed that the activity and the expression of the molecular circadian clock of Ae. aegypti differs significantly from that of mosquitoes subjected to constant or rectangular abrupt changes in temperature. We suggest that for understanding the circadian behaviour of Aedes with possible implications for intervention strategies, the semi-natural paradigm needs to replace the traditional laboratory study.